Identification and Risk-Stratification of Problem Alcohol Drinkers with Minor Trauma in the Emergency Department - Stewart, Scott H. (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2010)
BACKGROUND: Brief alcohol intervention may improve outcomes for injury patients with hazardous drinking but is less effective with increased severity of alcohol involvement. This study evaluated a brief method for detecting problem drinking in minor trauma patients and differentiating hazardous drinkers from those with more severe alcohol problems. METHODS: Subjects included 60 minor trauma patients in an academic urban emergency department (ED) who had consumed any amount of alcohol in the prior month. Screening and risk stratification involved the use of a heavy-drinking-day screening item and the Rapid Alcohol Problems Screen (RAPS). We compared the heavy-drinking-day item to past-month alcohol use, as obtained by validated self-reporting methods, and measured the percentage of carbohydrate-deficient transferrin (%CDT) to assess the accuracy of self-reporting. The Alcohol Dependence Scale (ADS) was administered to gauge the severity of alcohol involvement and compared to the RAPS. RESULTS: Eighty percent of the subjects endorsed at least one heavy drinking day in the past year, and all patients who exceeded recommended weekly drinking limits endorsed at least one heavy drinking day. Among those with at least one heavy drinking day, 58% had a positive RAPS result. Persons with no heavy drinking days (n=12) had a median ADS of 0.5 (range 0 to 3). RAPS-negative persons with heavy drinking days (n=20) had a median ADS of 2 (range 0 to 8). RAPS-positive persons with heavy drinking days (n=28) had a median ADS of 8 (range 1 to 43). CONCLUSION: A heavy-drinking-day item is useful for detecting hazardous drinking patterns, and the RAPS is useful for differentiating more problematic drinkers who may benefit from referral from those more likely to respond to a brief intervention. This represents a time-sensitive approach for risk-stratifying non-abstinent injury patients prior to ED discharge.